2023
DOI: 10.1111/cla.12561
|View full text |Cite
|
Sign up to set email alerts
|

The Chalcidoidea bush of life: evolutionary history of a massive radiation of minute wasps

Astrid Cruaud,
Jean‐Yves Rasplus,
Junxia Zhang
et al.

Abstract: Chalcidoidea are mostly parasitoid wasps that include as many as 500 000 estimated species. Capturing phylogenetic signal from such a massive radiation can be daunting. Chalcidoidea is an excellent example of a hyperdiverse group that has remained recalcitrant to phylogenetic resolution. We combined 1007 exons obtained with Anchored Hybrid Enrichment with 1048 ultra‐conserved elements (UCEs) for 433 taxa including all extant families, >95% of all subfamilies, and 356 genera chosen to represent the vast dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 136 publications
(284 reference statements)
0
13
0
Order By: Relevance
“…The phylogenetic analysis, not surprisingly because of their higher saturation [ 11 ], recovered serious polyphyly of all the major families of Chalcidoidea, which was divided into numerous clades ( Fig. 4B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phylogenetic analysis, not surprisingly because of their higher saturation [ 11 ], recovered serious polyphyly of all the major families of Chalcidoidea, which was divided into numerous clades ( Fig. 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…However, all families of Chalcidoidea were super-polyphyletic in both the ML and NJ phylogenetic trees. The polyphyly was expected because COI is generally a poor marker for a deep-time phylogenetic relationship, which is a fast-evolving marker with higher saturation [ 11 ]. A BLAST nucleotide search suggested that the parasitoid pupal sequence is closest to A. ceroplastae ; however, the identical base pair percentage was too low (88.4%) to be of the same species (recommended threshold: 2–3%; [ 24 , 40 ]).…”
Section: Discussionmentioning
confidence: 99%
“…According to the recently revised classification of Chalcidoidea by Burks et al (2022) and Cruaud et al (2024), most chalcidoid gallassociates are placed in the families Cynipencyrtidae, Epichrysomallidae, Melanosomellidae, Ormyridae and Tanaostigmatidae (Burks et al, 2022). Together, these taxa comprise the so called 'Gall Clade' sensu Burks et al (2022) and Cruaud et al (2024).…”
Section: Introductionmentioning
confidence: 99%
“…According to the recently revised classification of Chalcidoidea by Burks et al (2022) and Cruaud et al (2024), most chalcidoid gallassociates are placed in the families Cynipencyrtidae, Epichrysomallidae, Melanosomellidae, Ormyridae and Tanaostigmatidae (Burks et al, 2022). Together, these taxa comprise the so called 'Gall Clade' sensu Burks et al (2022) and Cruaud et al (2024). Cynipencyrtidae contains two enigmatic species: Cynipencyrtus flavus Ishii, a parasitoid of gall wasps (Cynipidae) (Ito & Hijii, 2000;Tachikawa, 1973Tachikawa, , 1978, and Cynipencyrtus indicus Singh collected from Quercus leucotrichophora forest (Singh, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many polyneopteran insects have larger genome sizes than holometabolous insect orders 16 , contributing to the general lack of genome sequencing projects in these groups. Molecular systematists studying Coleoptera, Diptera, Hymenoptera, and Lepidoptera were early adopters of this technique into their toolkits, resulting in ground-breaking phylogenomic studies with extensive taxon sampling 7,9,[17][18][19][20][21][22][23][24][25] . Now, pre-designed probes are commercially available for these insect orders.…”
Section: Introductionmentioning
confidence: 99%